Rewarding Honest Taxpayers? Evidence on the Impact of Rewards from Field Experiments - Lars P. Feld; Bruno S. Frey; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2006)
This paper analyzes the impact of rewards on tax compliance as an additional instrument to take into account. While social psychologists and neuroscientists have emphasized the importance of rewards, the tax compliance literature has strongly disregarded the possibilities of rewards. The use of field experiments presents an alternative ?carrot? strategy for tax policy. Design mechanisms to conduct a field experiments focusing on the impact of rewards on tax compliance are discussed.
Keywords: H26; H41; C90; D63; 330; positive rewards; tax compliance; tax evasion; field experiments